2014
DOI: 10.7863/ultra.33.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography for Liver Stiffness Measurement in Clinical Sonographic Examinations

Abstract: Objectives The purpose of this study was to determine the optimal minimum number of liver stiffness measurements on shear wave elastography (SWE) and to evaluate the frequency of technical failures and unreliable stiffness measurements and the intraobserver reproducibility of SWE. Methods This retrospective study was approved by our Institutional Review Board, and informed consent was waived. From August 2011 to January 2013, 540 patients underwent abdominal sonography, including SWE. In 86 patients (group 1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 51 publications
(75 reference statements)
5
42
0
3
Order By: Relevance
“…This is consistent with previous studies (Yoon et al, 2014; Poynard et al, 2013). High liver capsule depth means that the ultrasound waves have to travel through more intervening tissue to reach the liver, leading to more pre-liver attenuation and thus smaller applied force.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous studies (Yoon et al, 2014; Poynard et al, 2013). High liver capsule depth means that the ultrasound waves have to travel through more intervening tissue to reach the liver, leading to more pre-liver attenuation and thus smaller applied force.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, Shear Wave Elasticity Imaging (SWEI) (Sarvazyan et al, 1998), has found success in the staging of liver fibrosis (Palmeri et al, 2011, 2008: Lazebnik, 2008; Piscaglia et al, 2011; Friedrich-Rust et al, 2009; Haque et al, 2010; Horster et al, 2010; Lupsor et al, 2009; Fierbinteanu-Braticevici et al, 2009). However, studies routinely report depth penetration limitations and exclude patients with livers and hepatic lesions deeper than 6–8 cm (Park et al, 2013), and technical failure and unreliable measurement rates for liver stiffness have been reported to increase both with elevated patient BMI (a measure of obesity) (Yoon et al, 2014), and in the presence of significant hepatic fibrosis (Poynard et al, 2013). These challenges likely result from: (1) significant propagation distances of ultrasound waves through subcutaneous fat in patients with higher BMIs, which can attenuate acoustic radiation force impulse (ARFI) excitations and abberate tracking ultrasound beams, and (2) smaller displacement amplitudes in stiffer livers.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and validity of elastographic measurements have been investigated in several studies (Park et al, 2014, Yoon et al, 2014). Regarding the muscular tissues, in particular, the crural and the brachial muscles have been shown to have good measurement reliably with satisfactory ICCs (Brandenburg et al, 2015, Koo et al, 2013, Koo et al, 2014, Taniguchi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The technique is fast, convenient and applicable to a variety of clinical scenarios in which other approaches would potentially be inadequate. To date, it has been used successfully for breast cancers diagnosis (Athanasiou et al, 2010, Park et al, 2014) and liver fibrosis staging (Ferraioli et al, 2014, Yoon et al, 2014). In addition, quantitative assessments of material properties of muscles have also been investigated by in vivo and in vitro studies (Akagi and Kusama, 2015, Hirata et al, 2015, Hug et al, 2013, Miyamoto et al, 2015, Itoigawa et al, 2015, Koo et al, 2014, Akagi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is expected to overcome the limitations of transient elastography, where liver stiffness cannot be measured accurately in patients with severe obesity, and ascites. Some articles have shown growing evidence for the accuracy of US elastography [33][34][35][36][37] (Table 1). Although the low reproducibility of measurements derived from operator-dependent performance remains a significant limitation of US elastography, this technique is a useful diagnostic tool for hepatic fibrosis and further validation is warranted.…”
Section: A B Cmentioning
confidence: 99%